2017
DOI: 10.1093/arclin/acx033
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Ability and Short-term Memory, and Reading and Mathematics Achievement in Children

Abstract: These findings indicate the significant affect of psychomotor ability on learning outcomes and consequently the need to assess these in considering learning difficulties, and as such these findings also advance understanding of developmental neural mechanisms underpinning the relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
0
22
0
2
Order By: Relevance
“…One study by Geertsen et al [69] found that better performance in a gross motor task (i.e., a shorter time to complete a coordination wall task) was associated with better scores on a standardized mathematics test. Another study by Murrihy et al [75] reported a significant weak positive correlation (r = 0.26, p < 0.05) between a finger-to-nose test and a standardized mathematics test. However, a study by Van Niekerk [45] reported conflicting results, with a significant weak positive correlation (r = 0.23, p < 0.05) found between a task involving tapping feet and fingers and teacher-reported maths results for boys and girls, but no significant association found between a jumping-in-place task (same sides synchronized) and teacher-reported maths results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study by Geertsen et al [69] found that better performance in a gross motor task (i.e., a shorter time to complete a coordination wall task) was associated with better scores on a standardized mathematics test. Another study by Murrihy et al [75] reported a significant weak positive correlation (r = 0.26, p < 0.05) between a finger-to-nose test and a standardized mathematics test. However, a study by Van Niekerk [45] reported conflicting results, with a significant weak positive correlation (r = 0.23, p < 0.05) found between a task involving tapping feet and fingers and teacher-reported maths results for boys and girls, but no significant association found between a jumping-in-place task (same sides synchronized) and teacher-reported maths results.…”
Section: Resultsmentioning
confidence: 99%
“…A total of five studies [44,45,68,74,75] analysed the relationship between balance and academic performance in mathematics. One study [74] assessed balance using a static single leg balance task, reporting several significant very weak to weak positive correlations (r = 0.26–0.37) between the balance task and mathematical performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations